Hippocampal protein expression is differentially affected by chronic paroxetine treatment in adolescent and adult rats: a possible mechanism of “paradoxical” antidepressant responses in young persons - Karanges, Emily A.; Kashem, Mohammed A.; Sarker, Ranjana; Ahmed, Eakhlas U.; Ahmed, Selina; van Nieuwenhuijzen, Petra; Kemp, Andrew H.; McGregor, Iain S. (Frontiers in Pharmacology, 2013)
Selective serotonin reuptake inhibitors (SSRIs) are commonly recognised as the pharmacological treatment of choice for patients with depressive disorders, yet their use in adolescent populations has come under scrutiny following reports of minimal efficacy and an increased risk of suicidal ideation and behavior in this age group. The biological mechanisms underlying these effects are largely unknown. Accordingly, the current study examined changes in hippocampal protein expression following chronic administration of paroxetine in drinking water (target dose = 10 mg/kg for 22 days) to adult and adolescent rats. Results indicated age-specific changes in protein expression, with paroxetine significantly altering expression of 8 proteins in adolescents only and 10 proteins solely in adults. A further 12 proteins were significantly altered in both adolescents and adults. In adults, protein changes were generally suggestive of a neurotrophic and neuroprotective effect of paroxetine, with significant downregulation of apoptotic proteins Galectin 7 and Cathepsin B, and upregulation of the neurotrophic factor Neurogenin 1 and the antioxidant proteins Aldose reductase and Carbonyl reductase 3. Phosphodiesterase 10A, a signalling protein associated with major depressive disorder, was also downregulated (−6.5 fold) in adult rats. Adolescent rats failed to show the neurotrophic and neuroprotective effects observed in adults, instead displaying upregulation of the proapoptotic protein BH3-interacting domain death agonist (4.3 fold). Adolescent protein expression profiles also suggested impaired phosphoinositide signalling (Protein kinase C: −3.1 fold) and altered neurotransmitter transport and release (Syntaxin 7: 5.7 fold; Dynamin 1: −6.9 fold). The results of the present study provide clues as to possible mechanisms underlying the atypical response of human adolescents to paroxetine treatment.